2022
DOI: 10.1177/08465371221142515
|View full text |Cite
|
Sign up to set email alerts
|

Bringing Radiology Education to a New Reality: A Pilot Study of Using Virtual Reality as a Remote Educational Tool

Abstract: Purpose: We investigated virtual reality (VR) during a 2-week, undergraduate, radiology elective to determine if it improved learning outcomes and user satisfaction. Methods: Eighteen students enrolled between August 2021 and February 2022. Each student had a collaborative Zoom teaching session with a preceptor using a Picture Archive and Communications System (PACS)-like viewing system Online DICOM Image Navigator (ODIN), followed by a teaching session using a VR, Digital Imaging and Communications in Medicin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…Similarly, 58% of the respondents in the study conducted by O’Connor et al [ 15 ] reported enjoying learning using VR simulation. In the study by Wu et al [ 37 ], 83.3% of students agreed or strongly agreed that they enjoyed using VR for learning. Similarly, the studies by Rainford et al [ 31 ] and O’Connor et al [ 15 ] reported student recommendation of 87% and 94%, respectively, for VR as a learning tool.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, 58% of the respondents in the study conducted by O’Connor et al [ 15 ] reported enjoying learning using VR simulation. In the study by Wu et al [ 37 ], 83.3% of students agreed or strongly agreed that they enjoyed using VR for learning. Similarly, the studies by Rainford et al [ 31 ] and O’Connor et al [ 15 ] reported student recommendation of 87% and 94%, respectively, for VR as a learning tool.…”
Section: Resultsmentioning
confidence: 99%
“…The studies used a wide range of VR software and hardware. Some of the studies used 3D simulation software packages displayed on 2D desktop computers [ 22 24 25 36 ], whereas others used headsets for an immersive VR environment [ 15 23 26 35 37 ]. The most used VR teaching software were the CETSOL VR Clinic software [ 33 35 ], Virtual Medical Coaching VR software [ 15 30 32 ], Projection VR (Shaderware) software [ 36 ], SieVRt VR system (Luxsonic Technologies) [ 37 ], medical imaging training immersive environment software [ 23 ], VR CT Sim software [ 25 ], VitaSim ApS software [ 26 ], VR X-Ray (Skilitics and Virtual Medical Coaching) software [ 27 ], and radiation dosimetry VR software (Virtual Medical Coaching Ltd) [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…8 In a radiology elective for undergraduate students, Wu et al cited the cost of a high-fidelity VR workstation as $3,200 CAD and the software license as $600 CAD. 36 Another study found the cost per trainee to practice microsurgical techniques on a high fidelity, live rat vas deferens model was $55 CAD, while it was only $1.50 CAD for the low-fidelity, silicone tubing model. 27 Despite this cost difference, long-term patency rates were the same across both groups.…”
Section: Challenges and Limitations Of Simulation Use In Educationmentioning
confidence: 99%
“…35 VR use during a 2-week undergraduate diagnostic radiology elective found mixed results, with students performing better at limited tasks in part due to underlying technical challenges. 36 A separate group developed a VR training system using an endovascular robotic system; this may one day represent how IR is practiced, but it is limited to particular academic centers and is still very much a nascent technology. 37 Hayden et al described “telesimulation,” in which the instructor observes via webcam and remotely controls a mannequin being used to simulate a variety of cases.…”
Section: Simulation In Educationmentioning
confidence: 99%